COST EFFECTIVE CANCER TREATMENT- A NEED OF TODAY: COST EFFECTIVE CANCER TREATMENT - Hussain, Iftikhar; Nadeem, Muhammad (Pakistan Armed Forces Medical Journal, 2015)
The diagnosis of cancer raises an alarm not only in the mind of patient regarding the question of life and death but in the mind of the oncologist regarding the choices between low to high cost treatment options and in the mind of heath care funding agency regarding the overall cost of treatment. As the medical technology is advancing day by day, the cost of treatments are also rising exponentially. Among the most costly treatments oncology heads the list. The total economic impact of premature death and disability from cancer worldwide was  895 billion dollars in 2008 which is 1.5 percent of world’s gross domestic product1. The high prices of individual drugs are creating a difficult situation for patients, oncologists and the health care planners who are inadequately prepared for these challenges. They have to make difficult trade-offs between very high out-of-pocket costs and very expensive treatment with measurable but sometimes modest health benefits. As well, oncologists are often conflicted about how the cost of care should affect their behavior. The health care planners at the same time face the horns of dilemma while balancing the costly treatments with modest benefits on one hand and the relative low cost treatments with curative results in other diseases. This issue is complicated by the ever increasing number of the brands of drugs with differing rates and claim of equal potency to that of the brand leader. Even the most advanced and economically strong countries are facing this difficult situation and devising plans to address this issue. The American Society of Clinical Oncology, the world’s leading professional organization, established the cost of cancer care task force in 2007 to address the challenges related to cost of cancer care2. The task force, later renamed as value in cancer care task force, in its recent report   recommended multiple innovative models to identify the feasibility of high value cancer care against the rising costs2.The oncology services in Pakistan Armed Forces, as all other treatments, are free of cost for the patients. Anticancer medicines are costly medicines and constitute a significant share in budget allocation. Balancing efficacy and cost effectiveness to meet budget challenges as well as not compromising on patient`s health is a daunting task. No system existed previously to compare different brands of drugs in terms of their efficacy and cost effectiveness. Thus, there was a dire need of a fair and transparent policy to select suitable brands of anticancer drugs for procurement, in line with international guidelines. The oncology formulary committee was formulated at Combined Military Hospital Rawalpindi to address this issue. The committee was given the task to device a framework to objectively assess the brands of drugs available in terms of their efficacy and cost effectiveness. The committee recommended the merit evaluation methodology which puts greater emphasis on non-price factors like the high quality of a product that can be validated internationally. The quality of brands were assessed and weightages were given as per their qualification against the set standards called “priority level”. Priority one brands were those which were approved by and thus visible online on the websites of the drug regulatory authorities of the leading members of Pharmaceutical Inspection Co-operation Scheme. Priority 2 was assigned to the brands registered with the drug regulatory authorities of the other members of Pharmaceutical Inspection Co-operation Scheme. Priority 3 and 4 were the brands with a bio equivalence or chemical equivalence certificates respectively against the brand leader from an unbiased WHO accredited reference laboratory. Priority 5 was the brand with a publication of a trial of the drug in any indexed international medical journal showing the equivalence to the brand leader. Priority 6 was exception, when the only brand available would not meet any priority standard. Once the brands were assigned the quality standards then the price factor was given due consideration to choose two best quality and cost effective brands of each drug. In this way, a two brand formulary was recommended for one financial year. This effort has translated into an effective system of high quality cost effective management of patients with cancer. The impact on the financial budget has already started to become evident. The budget of anticancer drugs that was 269 million in 2010 with no validation of quality of brands has now dropped significantly to an average 170 million with brand validation.The improvement in diagnostic facilities and health awareness is increasing the number of patients with cancer dramatically each year. In the year 2014, approximately 2000 new cases have been registered at Combined Military Hospital Rawalpindi. Thus the patients requiring anticancer treatment will be rising in coming years. In order to continue to provide free anticancer treatment cost effective approach will be a cornerstone of future policy making.